The consequence of workplace incivility among IT employees: Workplace stress or organizational citizenship behavior? - Narayanan Annalakshmi; Philip Roshni; Sanjay Abhirami; Pant Udita (HUMANITAS published by Universitas Ahmad Dahlan., 2022)
The impact of the work environment on employees has been well researched, with little focus on the pathways of such relationships. This study aimed to examine whether workplace incivility and personality predict workplace stress and organizational citizenship behavior (OCB). The role of John Henryism (JH), Probabilistic Orientation (PO), work self-efficacy, and resilience on workplace stress and OCB was also explored. The data were collected through a survey using self-report measures of perception of fair interpersonal treatment in the workplace, workplace incivility, work self-efficacy, JH, PO, workplace stress, and OCB from 206 (M=120, F=86) employees from the IT industry, aged 22 to 42 (M=30.47, SD=5.60). Multiple regression analyses revealed that workplace incivility (from supervisor and client) positively predicted workplace stress. At the same time, coworker incivility did not predict workplace stress. On the contrary, workplace incivility (supervisor, coworker, and clients) did not predict OCB significantly. JH and work self-efficacy positively predicted OCB, while PO negatively predicted OCB. This research provides new directions for future research that workplace stress is predicted by supervisor and client incivility, and OCB is not predicted by workplace incivility.